2017
DOI: 10.1186/s12864-016-3480-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the mitochondrial genomes of Colletotrichum gloeosporioides sensu lato: insights into the evolution of a fungal species complex interacting with diverse plants

Abstract: BackgroundThe fungal species complex Colletotrichum gloeosporioides sensu lato contains over 20 plant-interacting species. These species exhibit different life styles (e.g., endophytes, foliar and fruit pathogens) and show considerable variation in host and tissue adaptation strategies. Accurate species delimitation in C. gloeosporioides s.l. is very challenging due to nascent lineage boundaries and phenotypic plasticity, which strongly impedes studies of the complex’s host-interaction biology. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Therefore, mitogenomic sequences might be useful tools for accurate species identification 57 . In comparison to species identifications based on phylogenetic analyses of single gene sequences, such as ITS or rRNA genes 14 , 15 , phylogenies based on combined mitochondrial genes are more reliable, because they include more genetic information 58 , 59 . Here, we inferred the phylogenetic relationships of 18 species of fungi based on 15 mitogenomic PCGs; this analysis recovered a well-supported tree topology divided into three main clusters, consistent with traditional morphological classifications.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mitogenomic sequences might be useful tools for accurate species identification 57 . In comparison to species identifications based on phylogenetic analyses of single gene sequences, such as ITS or rRNA genes 14 , 15 , phylogenies based on combined mitochondrial genes are more reliable, because they include more genetic information 58 , 59 . Here, we inferred the phylogenetic relationships of 18 species of fungi based on 15 mitogenomic PCGs; this analysis recovered a well-supported tree topology divided into three main clusters, consistent with traditional morphological classifications.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the growing body of mitogenome data suggests that variation in MGE number can follow the divergence of different fungal taxa (Brankovics et al, 2017;Liang et al, 2017;Fourie et al, 2018), offering great perspectives for future diagnostic purposes. Brankovics et al (2017) showed that mosaicism in intron patterns can support the separation of three phylogenetic species in F. oxysporum.…”
Section: Introductionmentioning
confidence: 99%
“…Fourie et al (2018) revealed significant differences in intron patterns among species from the Fusarium fujikuroi species complex (FFSC). Beyond Fusarium, recent studies on Colletotrichum mitogenomes indicated that intron content variation could improve cryptic species delimitation within this genus (Liang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…mitogenomes, however, none of them were found in mitogenomes outside of the C. gloeosporioides s.l. complex, highlighting their use for potential diagnostic purposes [211]. A species-specific pattern of intron distribution has been also observed in F. oxysporum [188] and Fusarium fujikuroi species complex (FFSC) [212].…”
Section: Perspectives Of Targeting Mtdna For Barcoding Of Plant Pathomentioning
confidence: 85%
“…The most recent study by Liang et al (2017) [211] evaluated the efficacy of mitogenome sequence in the delimitation of four taxonomically challenging cryptic species within Colletotrichum gloeosporioides sensu lato (C. gloeosporioides, C. fructicola, C. aenigma, and C. siamense s.l.). Reliable delimitation of phylogenetic species in C. gloeosporioides s.l.…”
Section: Perspectives Of Targeting Mtdna For Barcoding Of Plant Pathomentioning
confidence: 99%